A model to investigate the mechanisms underlying the emergence and development of independent sitting. Issue 4 (28th November 2014) - O'Brien, Kathleen M.; Zhang, Jing; Walley, Philip R.; Rhoads, Jeffrey F.; Haddad, Jeffrey M.; Claxton, Laura J.
Abstract When infants first begin to sit independently, they are highly unstable and unable to maintain upright sitting posture for more than a few seconds. Over the course of 3 months, the sitting ability of infants drastically improves. To investigate the mechanisms controlling the development of sitting posture, a single‐degree‐of‐freedom inverted pendulum model was developed. Passive muscle properties were modeled with a stiffness and damping term, while active neurological control was modeled with a time‐delayed proportional‐integral‐derivative (PID) controller. The findings of the simulations suggest that infants primarily utilize passive muscle stiffness to remain upright when they first begin to sit. This passive control mechanism allows the infant to remain upright so that active feedback control mechanisms can develop. The emergence of active control mechanisms allows infants to integrate sensory information into their movements so that they can exhibit more adaptive sitting.